An Appendiceal Neoplastic Lesion: Case Report and Implications for Colonoscopic Screening and Surveillance - Hugh J Freeman; Douglas L Webber; Adam T Meneghetti (Canadian Journal of Gastroenterology)
A 65-year-old man with a history of previously resected colonic adenomas had an apparent cecal lesion detected during colonoscopy. The polyp proved to be a tubulovillous adenoma with high-grade dysplasia involving most of the body of the appendix along with the base of the cecum. The appendiceal mucosa is biologically similar to the colonic mucosa, yet remains relatively ‘hidden’ in screening and surveillance studies, which suggests important implications for evolving detection strategies in the follow-up of patients with a previous colon polyp or cancer resections. Although endoscopic removal of the appendix has been reported, treatment of these localized appendiceal lesions requires a wide surgical excision.